Conditions for enhancing the encoding of an elementary motor memory by rTMS. Issue 3 (March 2015) - Buetefisch, C.M.; Howard, C.; Korb, C.; Haut, M.W.; Shuster, L.; Pergami, P.; Smith, C.; Hobbs, G.
Highlights Co-administration of low frequency primary motor cortex stimulation with rTMS enhances formation of motor memories. The enhancing effect of rTMS on the formation of motor memories depends on the frequency and time of the stimulus in relationship to the onset of the training movements. The training related improvement in kinematics above naïve levels supports the notion of M1 engagement in events leading to improved motor skills.